Method for supplying rubber composition containing fine cellulose fiber
During the rubber processing process, the loss of fine cellulose cells and rubber latex are formed and packaged into a multi-layer structure, the problem of uniform dispersion of fine cellulose cells in the rubber component is solved, and the processability and workability in the rubber processing plant is improved.
Patent Information
- Application Number
- JP2023145510
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2043-09-07
AI Technical Summary
The prior art is difficult to achieve uniform dispersion of fine cellulose cell loss in rubber components, making it difficult to obtain the expected effect in rubber processing plants under different process conditions.
By forming the fine cellulose cell loss with the rubber latex into an intermediate stirring product at the first stirring place and packaging it into a multilayer structure at the second stirring place, further stirring is performed without releasing or protective film to achieve uniform dispersion.
The uniform dispersion of fine cellulose cell loss in the rubber component is achieved, and the pressure combination in the unvulcanized state is avoided, which improves the processability and workability of the rubber processing plant.
Smart Images

Figure 2025038727000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for supplying a rubber composition containing fine cellulose fibers. [Background technology]
[0002] It is known that a rubber composition produced from a masterbatch containing a rubber component and a cellulose fiber has excellent mechanical strength. For example, Patent Document 1 describes that a rubber / short fiber masterbatch in which the short fibers are uniformly dispersed in the rubber can be obtained by mixing a dispersion obtained by fibrillating short fibers having an average fiber diameter of less than 0.5 μm in water with a rubber latex and drying the mixture, and that a rubber composition having an excellent balance between rubber reinforcement and fatigue resistance can be produced from the masterbatch. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-206864 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, unless fine cellulose fibers such as cellulose nanofibers are uniformly dispersed in a rubber composition, it is difficult for the expected effects to be achieved. Therefore, a method for supplying a rubber composition containing fine cellulose fibers that can be more easily and uniformly dispersed is desired so that uniform desired effects can be obtained in various rubber processing plants with different working conditions.
[0005] The present invention aims to provide a method for supplying a rubber composition containing fine cellulose fibers that can be easily and uniformly dispersed and that is likely to exhibit the desired effects, and also aims to provide a method for supplying a rubber composition that prevents compression bonding in an unvulcanized state and has excellent workability in rubber processing plants. [Means for solving the problem]
[0006] As a result of extensive investigations, the inventors of the present application have found that the problems can be solved by the following (1) to (8). (1) A method for supplying a rubber composition containing fine cellulose fibers, comprising the steps of: In a first kneading place, an intermediate kneaded product is obtained by molding a mixture of fine cellulose fibers having a length-weighted average fiber length of more than 400 nm and rubber latex into a sheet shape, The intermediate kneaded product is transported to a second kneading location in a multi-layered package form, The method for supplying a rubber composition comprises diluting the intermediate mixture in a second mixing location and further mixing the mixture. (2) The method for supplying a rubber composition according to (1), wherein the fine cellulose fibers have a length-weighted average fiber diameter of 1 nm or more and 20 nm or less. (3) The method for supplying a rubber composition according to either (1) or (2), wherein the intermediate kneaded product contains fine cellulose fibers in the range of 10 to 40% by weight. (4) The method for supplying a rubber composition according to either (1) or (3), characterized in that the intermediate kneaded product is laminated and packaged without being subjected to treatments such as coating with a release agent or attaching a protective film. (5) The method for supplying a rubber composition according to either (1) or (4), wherein the intermediate mixture is unvulcanized. (6) The method for supplying a rubber composition according to (1) or (2), wherein the intermediate mixture is formed into a sheet by a roll kneading method. (7) The method for supplying a rubber composition according to (1) or (2), wherein the fine cellulose is anion-modified. (8) The method for supplying a rubber composition according to (1) or (2), wherein the fine cellulose has not been subjected to a hydrophobization treatment. Effect of the Invention
[0007] According to the present invention, there can be provided a method for supplying a rubber composition containing fine cellulose fibers which can be easily and uniformly dispersed and which is likely to exhibit the desired effects, and there can be provided a method for supplying a rubber composition which prevents bonding in an unvulcanized state and has excellent workability in a rubber processing plant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [1. Raw materials for rubber composition] The raw materials for the rubber composition include at least fine cellulose fibers and a rubber component, and may include additives as necessary. Each raw material will be described below.
[0009] [1.1 Fine cellulose fibers] The fine cellulose fiber is a fine fibrous cellulose derived from a cellulose raw material. The fine fibrous cellulose is, for example, a dispersion liquid (1 wt%) of fine cellulose fiber, which has a light transmittance of 1 to 99% at an optical path length of 1 cm / 660 nm using a visible spectroscopic analyzer (UV-1800, manufactured by Shimadzu Corporation). Methods for producing fine cellulose fiber include a method of defibrating pulp and a method of chemically modifying the pulp before or after defibration (usually before defibration) as necessary. Fine cellulose fiber having a fiber diameter of the nano order is called cellulose nanofiber, and fine cellulose fiber having a fiber diameter of the micron order is called cellulose microfibril. The size of the fine cellulose fiber can be adjusted by the conditions of the micronization treatment and chemical modification treatment.
[0010] In addition, powdered cellulose does not become dispersed even when stirred in a solvent such as water, but rather settles, so it is not possible to measure the light transmittance of the dispersion, and therefore it is clearly distinguished from fine cellulose fibers.
[0011] [Example of fine cellulose fiber: Cellulose nanofiber] In this specification, cellulose nanofiber (CNF) refers to cellulose fiber having a fiber diameter on the nano-order, which is prepared through a micronization process.
[0012] The average fiber diameter (length-weighted average fiber diameter) of CNF is 500 nm or less, preferably 300 nm or less, more preferably 100 nm or less, even more preferably 50 nm or less, and particularly preferably 20 nm or less. The lower limit is not particularly limited, but is usually 1 nm or more, preferably 2 nm or more. Therefore, the average fiber diameter (length-weighted average fiber diameter) of CNF is usually 1 to 500 nm or 2 to 500 nm, preferably 2 to 300 nm or 2 to 100 nm, more preferably 1 to 50 nm, 1 to 30 nm, or 1 to 20 nm.
[0013] It is important that the average fiber length (length-weighted average fiber length) is more than 400 nm, preferably 420 nm or more, and more preferably 440 nm or more. The upper limit is preferably 3000 nm or less, more preferably 2000 nm or less, further preferably 1500 nm or less, 1000 nm or less, or 800 nm or less.
[0014] The average fiber diameter and average fiber length of the fine cellulose fibers can be obtained by averaging the fiber diameter and fiber length obtained from the observation of each fiber using a fractionator manufactured by Valmet Co., Ltd., a scanning electron microscope (SEM), an atomic force microscope (AFM), or a transmission electron microscope (TEM) appropriately selected according to the fiber diameter. When a fractionator is used, the average fiber diameter and average fiber length can be obtained as the length-weighted fiber width and the length-weighted average fiber length, respectively.
[0015] [Example of fine cellulose fiber: cellulose microfibril] In this specification, cellulose microfibrils (microfibrillated cellulose, MFC) refer to cellulose fibers having a fiber diameter on the micron order, which are prepared through a pulverization process.
[0016] The average fiber diameter of MFC is usually 500 nm or more, preferably 1 μm or more, and more preferably 3 μm or more. This allows it to exhibit higher water retention than unfibrillated cellulose fibers, and even a small amount can provide higher strength and yield improvement effects than finely fibrillated CNF. The upper limit of the average fiber diameter is preferably 60 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and even more preferably 20 μm or less, but there is no particular limit.
[0017] The average fiber length is usually 10 μm or more, preferably 20 μm or more, and more preferably 40 μm or more. The upper limit is not particularly limited, but is usually 3,000 μm or less, preferably 2,500 μm or less, more preferably 2,000 μm or less, and even more preferably 1,500 μm or less, 1,000 μm or less, 500 μm or less, 400 μm, or 200 μm or less.
[0018] [Degeneration] The fine cellulose fibers may be modified or unmodified. Modified fine cellulose fibers refer to fine cellulose fibers (e.g., cellulose nanofibers, cellulose microfibrils) in which at least one of the three hydroxyl groups contained in the glucose unit has been chemically modified (hereinafter simply referred to as "modified"). The chemical modification treatment sufficiently refines the cellulose fibers, and cellulose nanofibers with a uniform average fiber diameter can be obtained by defibration. Therefore, when compounded with a rubber component, a sufficient reinforcing effect can be exhibited. From this viewpoint, modified cellulose fibers are preferred.
[0019] Examples of the modification include oxidation, etherification, esterification such as phosphate esterification, silane coupling, fluorination, cationization, etc. Among these, oxidation (carboxylation), etherification, cationization, and esterification are preferred, and oxidation (carboxylation) is more preferred.
[0020] -Oxidation (carboxylation)- The oxidized fine cellulose fibers usually have a structure in which at least one of the carbon atoms having a primary hydroxyl group contained in the glucopyranose unit constituting the cellulose molecular chain (for example, the carbon atom having a primary hydroxyl group at the C6 position) is oxidized. The amount of carboxyl groups in the oxidized cellulose fibers or oxidized cellulose nanofibers is preferably 0.5 mmol / g or more, more preferably 0.8 mmol / g or more, and even more preferably 1.0 mmol / g or more, based on the bone dry mass. The upper limit of the amount is preferably 3.0 mmol / g or less, more preferably 2.5 mmol / g or less, and even more preferably 2.0 mmol / g or less. The amount of carboxyl groups is preferably 0.5 to 3.0 mmol / g, more preferably 0.8 to 2.5 mmol / g, and even more preferably 1.0 to 2.0 mmol / g. The amount of carboxyl groups can be adjusted by controlling the conditions for oxidizing the cellulose fibers (for example, the amount of oxidizing agent added, the reaction time). Furthermore, by controlling these conditions, the amounts of carboxylate groups and aldehyde groups can also be adjusted.
[0021] The amount of carboxyl groups can be calculated by the following procedure. Prepare 60 ml of a 0.5% by mass slurry (aqueous dispersion) of oxidized cellulose. Add 0.1 M aqueous hydrochloric acid to the prepared slurry to adjust the pH to 2.5. Then, add 0.05 N aqueous sodium hydroxide solution dropwise and measure the electrical conductivity until the pH reaches 11. Calculate the amount of carboxyl groups from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual, using the following formula: Amount of carboxyl group [mmol / g oxidized cellulose] = a [ml] x 0.05 / oxidized cellulose Base mass [g]
[0022] The oxidation method is not particularly limited, but an example is a method in which a cellulose raw material is oxidized in water using an oxidizing agent in the presence of an N-oxyl compound, a bromide, an iodide, or a mixture thereof. According to this method, the C6 position of the glucopyranose ring on the cellulose surface is selectively oxidized to generate at least one group selected from the group consisting of an aldehyde group, a carboxy group (-COOH), and a carboxylate group (-COO-). The concentration of the cellulose raw material during the reaction is not particularly limited, but is preferably 5% by mass or less.
[0023] The N-oxyl compound refers to a compound capable of generating a nitroxy radical. Examples of the nitroxyl radical include 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO) and its derivatives (e.g., 4-hydroxyTEMPO). Any compound can be used as the N-oxyl compound as long as it promotes the target oxidation reaction. The amount of the N-oxyl compound used is not particularly limited as long as it is a catalytic amount capable of oxidizing the raw cellulose. For example, the amount is preferably 0.01 mmol or more, more preferably 0.02 mmol or more, per 1 g of bone-dry cellulose raw material. The upper limit is preferably 10 mmol or less, more preferably 1 mmol or less, and even more preferably 0.5 mmol or less. The amount of the N-oxyl compound used is preferably 0.01 to 10 mmol, more preferably 0.01 to 1 mmol, and even more preferably 0.02 to 0.5 mmol, per 1 g of bone-dry cellulose raw material. The amount of the N-oxyl compound used in the reaction system is usually 0.1 to 4 mmol / L.
[0024] Bromides are compounds containing bromine, such as bromides of alkali metals that can be dissociated and ionized in water. Iodides are compounds containing iodine, such as iodides of alkali metals. The amount of bromide or iodide used can be selected within a range that can promote the oxidation reaction. The total amount of bromide and iodide is, for example, preferably 0.1 to 100 mmol, more preferably 0.1 to 10 mmol, and even more preferably 0.5 to 5 mmol, per 1 g of bone-dry cellulose raw material.
[0025] The oxidizing agent may be a known one, such as halogen, hypohalous acid, halous acid, perhalogen acid or their salts, halogen oxide, or peroxide. Among them, hypohalous acid or its salt is preferred, hypochlorous acid or its salt is more preferred, and sodium hypochlorite is preferred, because it is inexpensive and has a low environmental impact. The appropriate amount of the oxidizing agent to be used is, for example, preferably 0.5 to 500 mmol, more preferably 0.5 to 50 mmol, even more preferably 1 to 25 mmol, and even more preferably 3 to 10 mmol, per 1 g of bone-dry cellulose raw material. Also, for example, 1 to 40 mol is preferred per 1 mol of the N-oxyl compound.
[0026] In the oxidation process of the cellulose raw material, the reaction proceeds efficiently even under relatively mild conditions. Therefore, the reaction temperature is preferably 4 to 40°C, and may be about 15 to 30°C, i.e., room temperature. As the reaction proceeds, carboxyl groups are generated in the cellulose, and a decrease in the pH of the reaction solution is observed. In order to efficiently proceed with the oxidation reaction, it is preferable to add an alkaline solution such as an aqueous sodium hydroxide solution to maintain the pH of the reaction solution at about 8 to 12, or 10 to 11. The reaction medium is preferably water, because it is easy to handle and does not easily cause side reactions.
[0027] The reaction time in the oxidation reaction can be appropriately set according to the degree of progress of the oxidation, and is usually from 0.5 to 6 hours, for example, about 0.5 to 4 hours.
[0028] The oxidation reaction may be carried out in two stages. For example, the oxidized cellulose obtained by filtering after the completion of the first stage reaction can be oxidized again under the same or different reaction conditions, allowing efficient oxidation without reaction inhibition by table salt produced as a by-product in the first stage reaction.
[0029] Another example of the carboxylation (oxidation) method is a method in which a cellulose raw material is oxidized by contacting it with an ozone-containing gas (ozone oxidation). This oxidation reaction oxidizes at least the hydroxyl groups at positions 2 and 6 of the glucopyranose ring, and decomposes the cellulose chain. The ozone concentration in the ozone-containing gas is 50 to 250 g / m 3 is preferable, and 50 to 220 g / m 3 The amount of ozone added is preferably 0.1 to 30 parts by mass, and more preferably 5 to 30 parts by mass, based on 100 parts by mass of the solid content of the cellulose raw material. The ozone treatment temperature is preferably 0 to 50°C, and more preferably 20 to 50°C. The ozone treatment time is not particularly limited, but is about 1 to 360 minutes, and preferably about 30 to 360 minutes. When the ozone treatment conditions are within these ranges, it is possible to prevent the cellulose raw material from being excessively oxidized and decomposed, and the yield of oxidized cellulose is good.
[0030] After the ozone treatment, an additional oxidation treatment may be carried out using an oxidizing agent. The oxidizing agent used in the additional oxidation treatment is not particularly limited, but examples include chlorine compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfuric acid, and peracetic acid. The additional oxidation treatment may be carried out, for example, by dissolving these oxidizing agents in a polar organic solvent such as water or alcohol to prepare an oxidizing agent solution, and immersing the oxidized cellulose in the solution.
[0031] An example of a method for measuring the amount of carboxy groups is explained below. 60 mL of a 0.5% by mass slurry (aqueous dispersion) of oxidized cellulose is prepared, and a 0.1 M aqueous hydrochloric acid solution is added to adjust the pH to 2.5, after which a 0.05 N aqueous sodium hydroxide solution is added dropwise and the electrical conductivity is measured until the pH reaches 11. The amount of carboxy groups can be calculated using the following (Equation 2) from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual. (Equation 2): Amount of carboxyl group [mmol / g (oxidized cellulose or oxidized cellulose nanofiber)] = a [mL] × 0.05 / mass of oxidized cellulose or mass of oxidized cellulose nanofiber [g]
[0032] -Acid-type oxidized cellulose and desalting- Oxidized cellulose contains carboxy groups as a result of oxidation, but it may contain more acid-type carboxy groups (-COOH) than salt-type carboxy groups (e.g., -COO-, -COONa), or it may contain more salt-type carboxy groups than acid-type carboxy groups. The amount of salt-type carboxy groups and acid-type carboxy groups can be adjusted by desalting treatment. By desalting treatment, salt-type carboxy groups can be converted to acid-type carboxy groups. In this specification, oxidized cellulose (which has been desalted) is called acid-type oxidized cellulose, and oxidized cellulose (which has not been desalted, as described below) is called salt-type oxidized cellulose. Salt-type oxidized cellulose usually mainly contains salt-type carboxy groups. On the other hand, acid-type oxidized cellulose contains many acid-type carboxy groups, and the proportion of acid-type carboxy groups in the carboxy groups is preferably 40% or more, more preferably 60% or more, and even more preferably 85% or more. Acid-type oxidized cellulose can exhibit a superior reinforcing effect together with component C. The proportion of acid-type carboxy groups can be calculated by the following procedure.
[0033] 1) First, 250 mL of an aqueous dispersion of acid-type oxidized cellulose before desalting treatment with a solids concentration of 0.1% by mass is prepared. A 0.1 M aqueous hydrochloric acid solution is added to the prepared aqueous dispersion to adjust the pH to 2.5, and then a 0.1 N aqueous sodium hydroxide solution is added and the electrical conductivity is measured until the pH reaches 11. The amount of acid-type carboxyl groups and the amount of salt-type carboxyl groups, i.e., the total amount of carboxyl groups, is calculated using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual: Total amount of carboxyl groups (mmol / g oxidized cellulose (salt type)) = a (ml) × 0 .1 / mass of oxidized cellulose (salt type) (g) 2) Prepare 250 mL of an aqueous dispersion of desalted acid-type oxidized cellulose with a solids concentration of 0.1% by mass. Add 0.1 N aqueous sodium hydroxide solution to the prepared aqueous dispersion, and measure the electrical conductivity until the pH reaches 11. Calculate the amount of acid-type carboxyl groups from the amount of sodium hydroxide (b) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual, using the following formula: Amount of acid-type carboxyl groups (mmol / g acid-type oxidized cellulose) = b (ml) × 0.1 / acid type Mass of oxidized cellulose (g) 3) From the calculated total amount of carboxy groups and the amount of acid carboxy groups, the ratio of acid carboxy groups is calculated using the following formula. Proportion of acid-type carboxyl groups (%) = (amount of acid-type carboxyl groups / total amount of carboxyl groups) ×100
[0034] The timing of desalting may be any time after oxidation, and may be either before or after defibration (before or after step (2)), but is usually after oxidation, and preferably before step (2). Desalting is usually carried out by substituting salts (e.g., sodium salts) contained in the salt-type oxidized cellulose with protons. Examples of desalting methods include a method of adjusting the system to be acidic, and a method of removing oxidized cellulose by Examples of the method include a method of contacting the cation exchange resin with the cation exchange resin. In the method of adjusting the inside of the system to acidity, the pH of the system is adjusted to preferably 2 to 6, more preferably 2 to 5, and further preferably 2.3 to 5. To adjust the inside of the system to acidity, an acid (for example, inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, sulfurous acid, nitrous acid, phosphoric acid, etc.; organic acids such as acetic acid, lactic acid, oxalic acid, citric acid, formic acid, etc.) is usually used. After the addition of the acid, a washing treatment may be appropriately performed. As the cation exchange resin, either a strongly acidic ion exchange resin or a weakly acidic ion exchange resin may be used as long as the counter ion is H+. The ratio of the oxidized cellulose and the cation exchange resin when they are contacted is not particularly limited, and a person skilled in the art can set it appropriately from the viewpoint of efficient proton replacement. The cation exchange resin after contact can be recovered by a conventional method such as suction filtration.
[0035] -Etherification- Examples of the etherification include carboxyalkylation, methylation, ethylation, cyanoethylation, hydroxyethylation, hydroxypropylation, ethylhydroxyethylation, and hydroxypropylmethylation, with carboxyalkylation being preferred and carboxymethylation being more preferred.
[0036] Carboxyalkylated cellulose fibers usually have a structure in which at least one of the carbon atoms constituting the cellulose molecular chain (for example, the carbon atom having a primary hydroxyl group at the C6 position constituting the glucopyranose unit) is carboxymethylated.
[0037] The degree of carboxyalkyl substitution (DS, preferably the degree of carboxymethyl substitution) per anhydrous glucose unit of the carboxyalkylated cellulose is preferably 0.01 or more, 0.02 or more, or 0.05 or more, more preferably 0.10 or more, even more preferably 0.15 or more, even more preferably 0.20 or more, and particularly preferably 0.25 or more. This ensures a degree of substitution for obtaining the effect of chemical modification. The upper limit of the degree of substitution is preferably 0.50 or less, more preferably 0.45 or less, 0.40 or less, or 0.35 or less. This makes it difficult for the cellulose fiber to dissolve in water, and allows the fiber form to be maintained in water. Therefore, the degree of carboxyalkyl substitution is preferably 0.01 to 0.50, more preferably 0.01 to 0.45, even more preferably 0.02 to 0.40, 0.10 to 0.35, or 0.15 to 0.30.
[0038] The degree of substitution, for example, the degree of carboxymethyl substitution, can be measured by the following method. Approximately 2.0 g of carboxymethylated cellulose (bone dry) is weighed out and placed in a 300 mL Erlenmeyer flask with a stopper. 100 mL of a solution obtained by adding 100 mL of special-grade concentrated nitric acid to 1,000 mL of methanol is added, and the mixture is shaken for 3 hours to convert the salt-type carboxymethylated cellulose (hereinafter also referred to as "salt-type carboxymethylated cellulose") to the acid-type carboxymethylated cellulose (hereinafter also referred to as "acid-type carboxymethylated cellulose"). 1.5 to 2.0 g of acid-type carboxymethylated cellulose (bone dry) is weighed out and placed in a 300 mL Erlenmeyer flask with a stopper. The acid-type carboxymethylated cellulose is moistened with 15 mL of 80% methanol, 100 mL of 0.1 N NaOH is added, and the mixture is shaken at room temperature for 3 hours. Using phenolphthalein as an indicator, excess NaOH is back-titrated with 0.1 N H2SO4, and the degree of carboxymethyl substitution (DS) can be calculated by the following formula: A = [(100 × F - (0.1N H2SO4 (mL)) × F') × 0.1] / (acid-form CM Dry mass of cellulose (g) DS = 0.162 x A / (1-0.058 x A) A: The amount of 1N NaOH required to neutralize 1 g of acid-type carboxymethyl cellulose (mL) F': Factor of 0.1N H2SO4 F: Factor of 0.1N NaOH
[0039] The degree of carboxyalkyl substitution can be adjusted by controlling reaction conditions such as the amount of the carboxyalkylating agent to be reacted, the amount of the mercerizing agent, and the composition ratio of water to the organic solvent.
[0040] An example of the carboxyalkylation method is a method in which the cellulosic raw material as the starting material (bottom raw material) is mercerized and then etherified. Carboxymethylation will be explained below as an example.
[0041] Carboxymethylated cellulose can be produced by using unmodified cellulose fibers (cellulose raw material: for example, pulp) as a starting material, carrying out a mercerization treatment, and then carrying out an etherification reaction. The reaction is usually carried out in the presence of a solvent. As the solvent, for example, water, lower alcohols (e.g., methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, tertiary butanol) can be used alone or in a mixture of two or more kinds. When a lower alcohol is mixed, the mixing ratio of the lower alcohol is preferably 60 to 95% by mass. The amount of the solvent is about 3 times the amount of the cellulose raw material in mass conversion. The upper limit of the amount is not particularly limited, but is 20 times or less. The amount of the solvent is preferably 3 to 20 times the amount of the cellulose raw material in mass conversion.
[0042] Examples of the mercerizing agent include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide.
[0043] The amount of the mercerizing agent used is, in terms of moles, preferably 0.5 times or more, more preferably 1.0 times or more, and even more preferably 1.5 times or more per anhydrous glucose residue of the starting material. The upper limit of the amount is usually 20 times or less, preferably 10 times or less, and more preferably 5 times or less. The amount of the mercerizing agent used is, in terms of moles, preferably 0.5 to 20 times, more preferably 1.0 to 10 times, and even more preferably 1.5 to 5 times.
[0044] The reaction temperature for mercerization is usually 0° C. or higher, and preferably 10° C. or higher. The upper limit is usually 70° C. or lower, and preferably 60° C. or lower. The reaction temperature is usually 0 to 70° C., and preferably 10 to 60° C.
[0045] The reaction time of the mercerization is usually 15 minutes or more, preferably 30 minutes or more. The upper limit is usually 8 hours or less, preferably 7 hours or less. The reaction time is usually 15 minutes to 8 hours, preferably 30 minutes to 7 hours.
[0046] The etherification reaction is usually carried out by adding a carboxymethylating agent to the reaction system after mercerization, such as sodium monochloroacetate.
[0047] The amount of the carboxymethylating agent added is, in molar terms, preferably 0.05 times or more, more preferably 0.5 times or more, and even more preferably 0.8 times or more per glucose residue of the cellulose raw material. The upper limit of the amount is usually 10.0 times or less, preferably 5 times or less, and more preferably 3 times or less. The amount of the carboxymethylating agent added is, in molar terms, preferably 0.05 to 10.0 times, more preferably 0.5 to 5 times, and even more preferably 0.8 to 3 times.
[0048] The reaction temperature is usually 30° C. or higher, preferably 40° C. or higher. The upper limit is usually 90° C. or lower, preferably 80° C. or lower. The reaction temperature is usually 30 to 90° C., preferably 40 to 80° C. The reaction time is usually 30 minutes or longer, preferably 1 hour or longer. The upper limit is usually 10 hours or shorter, preferably 4 hours or shorter. The reaction time is usually 30 minutes to 10 hours, and preferably 1 hour to 4 hours. During the carboxymethylation reaction, the reaction solution may be stirred as necessary.
[0049] -Difference from carboxymethyl cellulose- It is preferable that the carboxyalkylated cellulose fiber maintains at least a part of its fibrous shape even when dispersed in water. The carboxyalkylated cellulose fiber is distinguished from carboxymethyl cellulose, which is a type of water-soluble polymer that dissolves in water and imparts viscosity. When an aqueous dispersion of carboxyalkylated cellulose fiber is observed with an electron microscope, a fibrous substance can be observed. On the other hand, when an aqueous dispersion of carboxymethyl cellulose, which is a type of water-soluble polymer, is observed, a fibrous substance is usually not observed. In addition, when anion-modified cellulose fiber is measured by X-ray diffraction, a peak of cellulose type I crystals can be observed, but when carboxymethyl cellulose powder, which is a water-soluble polymer, is similarly measured, cellulose type I crystals are usually not observed.
[0050] -Acid-type carboxyalkylated cellulose and desalted materials- Carboxyalkylated cellulose may contain more acid-type carboxy groups than salt-type carboxy groups, or may contain more salt-type carboxy groups than acid-type carboxy groups. The amount of salt-type carboxy groups and acid-type carboxy groups can be adjusted by desalting treatment. By desalting treatment, salt-type carboxy groups can be converted to acid-type carboxy groups. In this specification, carboxyalkylated cellulose (which has been desalted) is called acid-type carboxyalkylated cellulose, and carboxyalkylated cellulose (which has not been desalted as described below) is called salt-type carboxyalkylated cellulose. Salt-type carboxyalkylated cellulose usually has salt-type carboxy groups (-COO-) as its main group. On the other hand, acid-type carboxyalkylated cellulose has many acid-type carboxy groups, and the ratio of the amount of acid-type carboxy groups to the amount of carboxy groups of acid-type carboxyalkylated cellulose is preferably 40% or more, more preferably 60% or more, and even more preferably 85% or more. The method for calculating the ratio of acid-type carboxy groups is as described above.
[0051] The timing of desalting is usually after carboxyalkylation, preferably after etherification and before fibrillation. For example, the desalting method may be a method of contacting carboxyalkylated cellulose with a cation exchange resin. As the cation exchange resin, either a strong acid ion exchange resin or a weak acid ion exchange resin can be used as long as the counter ion is H+. The ratio of the two when contacting carboxyalkylated cellulose with a cation exchange resin is not particularly limited, and a person skilled in the art can appropriately set it from the viewpoint of efficient proton replacement. For example, the ratio can be adjusted so that the pH of the aqueous dispersion after adding the cation exchange resin to the carboxyalkylated cellulose aqueous dispersion is preferably 2 to 6, more preferably 2 to 5. The cation exchange resin after contact may be recovered by a conventional method such as suction filtration.
[0052] -Esterification (phosphate esterification)- A first example of the esterified cellulose fiber is phosphorylated cellulose fiber. Phosphorylated cellulose usually has a structure in which at least one of the carbon atoms constituting the cellulose molecular chain (for example, the carbon atom having a primary hydroxyl group at the C6 position constituting the glucopyranose unit) is phosphorylated.
[0053] The amount of ionic substituent introduced into the phosphorylated cellulose fiber (ionic substituent amount, phosphorus oxo acid substituent amount) may be 0.10 mmol / g or more per 1 g (mass) of phosphorylated CNF, preferably 0.20 mmol / g or more, more preferably 0.30 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.50 mmol / g or more, even more preferably 0.60 mmol / g or more, and particularly preferably 0.70 mmol / g or more. The amount of ionic substituent introduced into the phosphorylated CNF may be 1.50 mmol / g or less per 1 g (mass) of cellulose fiber, preferably 1.35 mmol / g or less, more preferably 1.20 mmol / g or less, and even more preferably 1.10 mmol / g or less. The amount of ionic substituent introduced into the phosphated cellulose fiber is also preferably 1.00 mmol / g or less, more preferably 0.95 mmol / g or less, per gram (mass) of the phosphated cellulose fiber. Here, the denominator in the unit mmol / g indicates the mass of the cellulose fiber when the counter ion of the ionic substituent is a hydrogen ion (H+). The amount of phosphorus oxo acid substituent can be measured by the following method.
[0054] [Measurement of phosphorus oxoacid group content] The amount of phosphorus oxoacid groups in the fine cellulose fibers can be measured by diluting a fine cellulose fiber dispersion containing the target fine cellulose fibers with ion exchange water to a content of 0.2 mass% to prepare a cellulose fiber-containing slurry, treating the slurry with an ion exchange resin, and then titrating the slurry with an alkali.
[0055] Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above cellulose fiber-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry.
[0056] The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution to the cellulose fiber-containing slurry after the ion exchange resin treatment at 5 seconds, and measuring the change in the pH value of the slurry. Nitrogen gas was blown into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (differential value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the alkali addition is called the first end point, and the second maximum point of the increment is called the second end point. The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point was divided by the solid content (g) in the slurry to be titrated to determine the amount of phosphorus oxoacid groups (mmol / g). The presence or absence of introduction of phosphate groups was confirmed by measuring the infrared absorption spectrum and observing the absorption due to phosphate groups (1230 cm -1 This may be done by checking the surrounding area.
[0057] The amount of phosphate groups can be adjusted by controlling reaction conditions such as the amount of the compound having a phosphate group added and the amount of the basic compound added as needed.
[0058] Examples of the phosphorylation method include a method of reacting a compound having a phosphoric acid group with unmodified cellulose fibers (phosphorylation). Examples of the phosphorylation method include a method of mixing a powder or an aqueous solution of a compound having a phosphoric acid group with a cellulosic raw material (for example, a suspension (solid content concentration is about 0.1 to 10% by mass)) and a method of adding an aqueous solution of a compound having a phosphoric acid group to an aqueous dispersion of the cellulosic raw material, the latter being preferred. This can increase the uniformity of the reaction and the efficiency of esterification. The pH of the aqueous solution of the compound having a phosphoric acid group is preferably 7 or less from the viewpoint of increasing the efficiency of introduction of the phosphoric acid group, and more preferably 3 to 7 from the viewpoint of suppressing hydrolysis.
[0059] Examples of compounds having a phosphate group include phosphoric acid, polyphosphoric acid, phosphorous acid, phosphonic acid, polyphosphonic acid, esters and salts thereof. These compounds are low cost and easy to handle, and can be introduced into cellulose to improve defibration efficiency. Specific examples of compounds having a phosphate group include phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium metaphosphate. Compounds having a phosphate group can be used alone or in combination of two or more. The amount of the compound having a phosphate group added to the cellulose raw material is preferably 0.1 to 500 parts by mass, more preferably 1 to 400 parts by mass, and even more preferably 2 to 200 parts by mass in terms of phosphorus element, relative to 100 parts by mass of the solid content of the cellulose raw material. This makes it possible to efficiently obtain a yield that corresponds to the amount of the compound having a phosphate group used. The reaction temperature is preferably 0 to 95°C, more preferably 30 to 90°C. The reaction time is not particularly limited, but is usually about 1 to 600 minutes, preferably 30 to 480 minutes. When the esterification reaction conditions are within any of these ranges, it is possible to prevent the cellulose from being excessively esterified and becoming easily soluble, and to improve the yield of the phosphorylated cellulose. When reacting a compound having a phosphoric acid group, a basic compound (for example, a compound having an amino group that shows basicity, such as urea, methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, or hexamethylenediamine) may be further added to the reaction system.
[0060] The suspension obtained after esterification is dehydrated as necessary, and preferably subjected to a heat treatment after dehydration. This can suppress hydrolysis of the cellulose raw material. The heating temperature is preferably 100 to 170°C, and while water is contained during the heat treatment, it is more preferable to heat at 130°C or less (preferably 110°C or less), remove the water, and then perform heat treatment at 100 to 170°C. After boiling, it is preferable to perform a washing treatment such as washing with cold water and / or a neutralization treatment. This allows efficient defibration. Washing may be performed by adding water and then dehydrating (for example, filtration), and may be repeated two or more times. Washing is preferably performed until the electrical conductivity of the filtrate decreases. For example, it can be performed until the electrical conductivity is preferably 200 or less, more preferably 150 or less, and even more preferably 120 or less. After washing, a neutralization treatment may be performed as necessary. The neutralization treatment can be performed by adding an alkali (for example, sodium hydroxide). Washing may be performed again after neutralization.
[0061] -Esterification (phosphite esterification)- A second example of the method for producing esterified cellulose fibers is phosphite-esterified cellulose fibers. Phosphite-esterified cellulose fibers usually have a structure in which at least one of the carbon atoms constituting the cellulose molecular chain (for example, the carbon atom having a primary hydroxyl group at the C6 position constituting the glucopyranose unit) is phosphorylated.
[0062] The degree of substitution of the phosphite group per glucose unit in the phosphite esterified cellulose fiber (hereinafter simply referred to as the "degree of substitution of the phosphite group") is preferably 0.001 to 0.60. This makes it easier for electrical repulsion to occur between cellulose molecules, facilitating nanofibrillation. The degree of substitution of the phosphite group can be measured by the same method as that for measuring the degree of substitution of the phosphate group. The degree of substitution of the phosphite group can be adjusted by controlling reaction conditions such as the amount of phosphorous acid or a salt thereof added, the amount of an alkali metal ion-containing material used as necessary, and the amount of urea or a derivative thereof added.
[0063] An example of a method for phosphite esterification is a method in which phosphorous acid or a metal salt thereof (preferably sodium hydrogen phosphite) is reacted with unmodified cellulose fibers to introduce an ester group of phosphorous acid.
[0064] Examples of phosphorous acid and its metal salts include phosphorous acid compounds such as phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, and pyrophosphorous acid, and combinations of two or more selected from these, with sodium hydrogen phosphite being preferred. This allows alkali metal ions to be introduced into the cellulose fibers. The amount of phosphorous acid or its metal salts added is preferably 1 to 10,000 g, more preferably 100 to 5,000 g, and even more preferably 300 to 1,500 g, per kg of unmodified cellulose fibers. In addition to phosphorous acid and its metal salts, an alkali metal ion-containing material (e.g., hydroxide, metal sulfate, metal nitrate, metal chloride, metal phosphate, and metal carbonate) may be further added to the reaction system.
[0065] Urea or a derivative thereof may be further added to the reaction system. This allows the introduction of carbamate groups into the cellulose fibers. Examples of urea and urea derivatives include urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea, and combinations of two or more selected from these, with urea being preferred. The amount of urea and urea derivatives added is preferably 0.01 to 100 mol, more preferably 0.2 to 20 mol, and even more preferably 0.5 to 10 mol, per mol of phosphorous acid or its metal salt.
[0066] The reaction temperature is preferably 100 to 200°C, more preferably 100 to 180°C, and even more preferably 100 to 170°C. During the heat treatment, while water is contained, it is more preferable to heat at 130°C or less (preferably 110°C or less), remove the water, and then heat treat at 100 to 170°C. The reaction time is usually about 10 to 180 minutes, more preferably 30 to 120 minutes. The phosphite esterified cellulose fiber is preferably washed prior to defibration. The degree of substitution of phosphite groups per glucose unit is preferably 0.01 or more and less than 0.23.
[0067] -Esterification (sulfate esterification)- A third example of the method for producing esterified cellulose fibers is cellulose sulfate fibers. Cellulose sulfate usually has a structure in which at least one of the carbon atoms constituting the cellulose molecular chain (for example, the carbon atom having a primary hydroxyl group at the C6 position constituting the glucopyranose unit) is phosphorylated.
[0068] The amount of sulfate groups per glucose unit in the sulfated cellulose fiber (hereinafter simply referred to as "amount of sulfate groups") is preferably 0.42 to 9.9 mmol / g, more preferably 0.5 mmol / g to 2.0 mmol / g. By introducing sulfate groups into the cellulose raw material, cellulose particles repel each other electrically. Therefore, the sulfated cellulose having sulfate groups introduced therein can be easily defibrated into nanofibers. When the amount of sulfate groups is 0.42 mmol / g or more, the cellulose particles can be sufficiently defibrated into nanofibers due to the electrical repulsion between the cellulose particles. On the other hand, when the amount of sulfate groups is 9.9 mmol / g or less, swelling or dissolution can be suppressed, and a situation in which the nanofibers cannot be obtained can be prevented. In order to perform defibration efficiently, it is preferable to wash the sulfated cellulose obtained above.
[0069] The amount of sulfate groups per glucose unit can be measured by the following method. The aqueous dispersion of sulfated CNF is subjected to solvent replacement with ethanol and then t-butanol, and then freeze-dried. 15 ml of ethanol and 5 ml of water are added to 200 mg of the obtained sample, and the mixture is stirred for 30 minutes. Then, 10 ml of 0.5N aqueous sodium hydroxide solution is added, and the mixture is stirred at 70°C for 30 minutes and further stirred at 30°C for 24 hours. Next, phenolphthalein is added as an indicator, and titration is performed with hydrochloric acid, and the amount of sulfate groups per glucose unit is calculated using the following formula: Amount of sulfate group [mmol / g sample] = (5 - (0.1 x titration amount of hydrochloric acid [ml] x 2)) / 0.2
[0070] The amount of sulfate groups can be adjusted by controlling reaction conditions such as the amount of the sulfate compound to be reacted.
[0071] As a method of sulfate esterification, for example, there is a method in which a sulfate group derived from the sulfate compound is introduced into cellulose by reacting unmodified cellulose fibers with the sulfate compound to obtain sulfated cellulose. Examples of the sulfate compound include sulfuric acid, sulfamic acid, chlorosulfonic acid, sulfur trioxide, and esters or salts thereof. Among these, it is preferable to use sulfamic acid because it has low solubility in cellulose and low acidity.
[0072] For example, when sulfamic acid is used as the sulfate compound, the amount of sulfamic acid used can be appropriately adjusted in consideration of the amount of anion groups introduced into the cellulose chain, and is preferably 0.01 to 50 mol, more preferably 0.1 to 3.0 mol per mol of glucose unit in the cellulose molecule.
[0073] -Salt type / Acid type- The esterified cellulose may contain more acid-type carboxy groups than salt-type carboxy groups, or may contain more salt-type carboxy groups than acid-type carboxy groups. Among esterified cellulose, those that have not been subjected to desalting treatment and those that have been subjected to desalting treatment are called salt-type esterified cellulose and acid-type esterified cellulose, respectively. Salt-type esterified cellulose mainly has salt-type carboxy groups. It is presumed that acid-type esterified cellulose has a superior reinforcing effect due to the component C. The counter cation of the salt-type carboxy group and the preparation method thereof are as explained in the explanation of oxidized cellulose.
[0074] -Cationization- Cationic cellulose usually has a structure in which at least one of the carbon atoms constituting the cellulose molecular chain (for example, the carbon atom having a primary hydroxyl group at the C6 position constituting the glucopyranose unit) is cationized, and usually contains a cation such as ammonium, phosphonium, or sulfonium, or a group having such a cation, in the molecule. The degree of cationic substitution per glucose unit in cationized cellulose is preferably 0.02 to 0.50. The degree of cationic substitution per glucose unit can be measured by the following method. After drying the cationized cellulose fiber, the nitrogen content is measured using a total nitrogen analyzer (TN-10 manufactured by Mitsubishi Chemical Corporation), and the degree of cationic substitution (the average number of moles of substituents per mole of anhydrous glucose unit) is calculated by the following formula: Degree of cation substitution = (162 x N) / (1-151.6 x N) N: Nitrogen content
[0075] The degree of cationic substitution can be adjusted by adjusting reaction conditions such as the amount of the cationizing agent to be reacted and the composition ratio of water or the alcohol having 1 to 4 carbon atoms.
[0076] An example of a method for cationization is a method in which unmodified cellulose fibers are reacted with a cationization agent (e.g., glycidyl trimethylammonium chloride, 3-chloro-2-hydroxypropyl trialkylammonium hydrite or a halohydrin type thereof) and an alkali metal hydroxide (e.g., sodium hydroxide, potassium hydroxide) as a catalyst in the presence of water and / or an alcohol having 1 to 4 carbon atoms. By using any of the cationization agents exemplified above, it is possible to obtain a cationized cellulose having a group containing a quaternary ammonium. The cationization reaction is usually carried out in the presence of water or an alcohol.
[0077] The amount of the cationizing agent is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, based on 100 parts by mass of the cellulose raw material. The upper limit of the amount is usually 800 parts by mass or less, preferably 500 parts by mass or less.
[0078] Examples of catalysts that may be used as necessary during cationization include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide. The amount of catalyst is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, based on 100 parts by mass of the cellulose raw material. The upper limit of the amount is usually 7 parts by mass or less, preferably 3 parts by mass or less.
[0079] -Base-type cationized cellulose fiber- The cationized cellulose fibers after cationization are preferably converted to base-type cationized cellulose or base-type cationized cellulose nanofibers by desalting. The salt in the cationized cellulose can be converted to a base by desalting. In this specification, cationized cellulose (nanofibers) that have been desalted are referred to as base-type cationized cellulose (nanofibers) or cationized cellulose (nanofibers) (base type). Moreover, cationized cellulose and cationized cellulose nanofibers that have not been desalted are referred to as salt-type cationized cellulose (nanofibers) or cationized cellulose (nanofibers) (salt type). Desalting may be performed at any time before (cationized cellulose) or after (cationized cellulose nanofibers) defibration, which will be described later. Desalting means that the salt (e.g. Cl-) contained in the cationized cellulose (salt type) and the cationized cellulose nanofibers (salt type) is replaced with a base to make it a base type. As a desalting method after cationization, for example, a method of contacting the cationized cellulose or cationized cellulose nanofibers with an anion exchange resin can be mentioned. The anion exchange resin may be either a strong basic ion exchange resin or a weak basic ion exchange resin, as long as the counter ion is OH-. The ratio of the modified cellulose and the anion exchange resin when they are brought into contact with each other is not particularly limited, and a person skilled in the art can appropriately set the ratio from the viewpoint of efficiently carrying out cation exchange. As one example, the ratio can be adjusted so that the pH of the aqueous dispersion after addition of the anion exchange resin to the aqueous dispersion of cationized cellulose nanofibers is preferably 8 to 13, more preferably 9 to 13. The anion exchange resin after contact can be recovered by a conventional method such as suction filtration.
[0080] [Fine processing (defibration, fibrillation)] The pulverization is usually carried out by a mechanical treatment, preferably a beating or defibration treatment, which is usually carried out wet (i.e. in the form of an aqueous dispersion of cellulose fibres). Examples of equipment used for mechanical treatment include equipment capable of imparting mechanical defibration force, such as refiners (e.g., disk type, conical type, cylindrical type), high-speed defibrators, shear-type agitators, colloid mills, high-pressure jet dispersers, beaters, PFI mills, kneaders, dispersers, high-speed disintegrators (top finers), high-pressure or ultra-high-pressure homogenizers, grinders (stone-type grinders), ball mills, vibration mills, bead mills, single-axis, twin-axis, or multi-axis kneaders / extruders (homogenizers under high-speed rotation), refiners, defibrators, friction grinders, high-share defibrators, dispergers, and homogenizers (e.g., microfluidizers), among which equipment capable of imparting defibration force in a wet manner is preferred, and high-speed disintegrators and refiners are more preferred, but are not particularly limited.
[0081] When defibration is performed by a wet method, an aqueous dispersion of cellulose fibers is usually prepared. The solid content concentration of the modified cellulose in the aqueous dispersion is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1.0% by mass or more, and even more preferably 1.5% by mass or more. The upper limit of the concentration is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less. During the mechanical treatment, pH adjustment (for example, 7 or less, 6 or less, 5 or less) may be performed as necessary.
[0082] Prior to the preparation of the aqueous dispersion, a pretreatment such as dry pulverization (e.g., pulverization after drying) may be performed. Examples of the apparatus used for dry pulverization include, but are not limited to, impact mills such as hammer mills and pin mills, media mills such as ball mills and tower mills, and jet mills. In addition, a posttreatment may be performed after defibration. Examples of the posttreatment include, but are not limited to, drying (e.g., freeze drying, spray drying, tray drying, drum drying, belt drying, thin spreading on a glass plate or the like and drying, fluidized bed drying, microwave drying, heated fan reduced pressure drying, and reduced pressure (degassing) drying), redispersion in water (dispersion apparatus is not limited), and pulverization (e.g., pulverization using equipment such as a cutter mill, hammer mill, pin mill, or jet mill).
[0083] [Solids] The fine cellulose fibers may be in the form of an aqueous dispersion obtained after production, or may be a dry solid or wet solid of the dispersion. Examples of methods for preparing the dry solid or wet solid include drying (e.g., freeze drying, spray drying, tray drying, drum drying, belt drying, a method of thinly spreading on a glass plate or the like and drying, fluidized bed drying, microwave drying, and heated fan reduced pressure drying). The dry solid or wet solid may contain a water-soluble polymer. This can improve redispersibility. Examples of water-soluble polymers include cellulose derivatives (e.g., carboxymethylcellulose, methylcellulose, hydroxypropylcellulose, or ethylcellulose or salts thereof), xanthan gum, xyloglucan, dextrin, dextran, carrageenan, locust bean gum, alginic acid, alginates, pullulan, starch, potato starch, kudzu flour, cationic starch, phosphorylated starch, corn starch, gum arabic, locust bean gum, gellan gum, polydextrose, pectin, chitin, water-soluble chitin, chitosan, casein, albumin, soybean protein lysate, peptidase, glycerin, glyceryl stearate ... The term "polyvinyl alcohol", "polyacrylamide", "sodium polyacrylate", "polyvinylpyrrolidone", "polyvinyl acetate", "polyamino acids", "polylactic acid", "polymalic acid", "polyglycerin", "latex", "rosin-based sizing agents", "petroleum resin-based sizing agents", "urea resins", "melamine resins", "epoxy resins", "polyamide resins", "polyamide-polyamine resins", "polyethylenimine", "polyamines", "vegetable gums", "polyethylene oxide", hydrophilic crosslinked polymers, polyacrylates, starch-polyacrylic acid copolymers, tamarind gum, gellan gum, pectin, guar gum, and colloidal silica, as well as mixtures of one or more of these. Among these, carboxymethylcellulose or a salt thereof is preferably used in terms of compatibility.
[0084] After production, the fine cellulose fibers may be subjected to post-treatment such as redispersion in a dispersion medium such as water or alcohol (the dispersion device is not limited), or pulverization (e.g., pulverization using equipment such as a cutter mill, hammer mill, pin mill, or jet mill).
[0085] [Physical properties of fine cellulose fibers] The fine cellulose fibers preferably have the following physical properties.
[0086] -Specific surface area- The BET specific surface area of the fine cellulose fibers is preferably 10 m 2 / g or more, more preferably 50m 2 / g or more, more preferably 100m 2 The BET specific surface area can be measured by substituting t-BuOH for the aqueous dispersion and then freeze-drying the sample according to the nitrogen gas adsorption method (JIS Z 8830) using a BET specific surface area meter.
[0087] -Crystallization degree of cellulose type I- The crystallinity of cellulose type I in fine cellulose fibers is usually 50% or more, preferably 60% or more. There is no particular upper limit, but in reality it is thought to be about 90%. The crystallinity of cellulose can be controlled by the degree of chemical modification. The crystallinity of cellulose type I can be calculated by measuring and comparing the intensities of the (200) peak at around 22.6° and the valley between (200) and (110) (around 18.5°) by X-ray diffraction measurement.
[0088] -viscosity- When the fine cellulose fibers are dispersed in water, it is preferable that the viscosity of the water dispersion is low. This allows the material to have good handleability despite being fibrillated. For example, the B-type viscosity (25°C, 60 rpm) of an aqueous dispersion having a solid content of 1% by mass is usually 4,000 mPa·s or less or 3,000 mPa·s or less, preferably 2,500 mPa·s or less, and more preferably 2,000 mPa·s or less. The lower limit is preferably 10 mPa·s or more, more preferably 20 mPa·s or more, and even more preferably 50 mPa·s or more, 100 mPa or more, 500 mPa or more, 1,000 mPa or more, or 1,500 mPa or more. The B-type viscosity can be measured, for example, by the following method. After fibrillation (e.g., defibration), leave the mixture to stand for at least one day, dilute as necessary, and stir using a homodisper (e.g., 3000 rpm, 5 min), after which measure the viscosity (measure the viscosity after rotating at 60 rpm for 3 minutes).
[0089] -Water retention capacity- When the fine cellulose fibers are cellulose microfibrils, the water retention capacity is preferably 10 or more, more preferably 15 or more, even more preferably 20 or more, and even more preferably 30 or more. The upper limit is thought to be about 200 or less in reality, but is not particularly limited. The water retention capacity corresponds to the mass of water in the sediment relative to the mass of the solid content of the fibers in the sediment, and is the ratio of the water content to the solid content in the precipitated gel, measured and calculated by centrifuging a 0.3 mass% aqueous dispersion of the fibers at 25,000 G. That is, it is calculated by the following formula: Water retention capacity=(B+C-0.003×A) / (0.003×AC) A: Mass of an aqueous dispersion of cellulose microfibrils having a solids concentration of 0.3% by mass B: The mass of water dispersion A was centrifuged at 25,000 G for 30 minutes at 30°C. Mass of sediment to be deposited C: Mass of solids in the aqueous phase separated after the centrifugation
[0090] The higher the water retention value, the stronger the fiber's ability to retain water. Water retention can be measured or calculated for fibers that have undergone fibrillation, but cannot usually be measured for fibers that have not undergone fibrillation or defibration, or for cellulose nanofibers that have been defibrated to single microfibrils. When cellulose fibers that have not been fibrillated or defibrated are centrifuged under the above conditions, a dense sediment cannot be formed, and it is difficult to separate the sediment from the aqueous phase. When cellulose nanofibers are centrifuged under the above conditions, they usually hardly settle.
[0091] -Fibrillation rate- When the fine cellulose fibers are cellulose microfibrils, the fibrillation rate (Fibrillation %) is preferably 1.0% or more, more preferably 1.2% or more, and even more preferably 1.5% or more. This allows confirmation that fibrillation is sufficient. The fibrillation rate can be adjusted depending on the type of cellulose-based raw material used. The fibrillation rate can be determined by an image analysis type fiber analyzer such as a fractionator manufactured by Valmet Co., Ltd.
[0092] -Electrical conductivity- The electrical conductivity of the aqueous dispersion of fine cellulose fibers (solid content concentration 1.0% by mass) is preferably 500 mS / m or less, more preferably 300 mS / m or less, even more preferably 200 mS / m or less, even more preferably 100 mS / m or less, and particularly preferably 70 mS / m or less. The lower limit is preferably 5 mS / m or more, more preferably 10 mS / m or more. The electrical conductivity can be measured by preparing 200 g of an aqueous dispersion of fine cellulose fibers with a solid content concentration of 1.0% by mass and using an electrical conductivity meter (HORIBA ES-71 type).
[0093] - Degree of polymerization - The degree of polymerization of the fine cellulose fibers of the present invention, as measured by a viscosity method using a copper ethylenediamine solution, is preferably in the range of 250 to 1000, more preferably 300 to 900, and even more preferably 350 to 800. Within such a range, the viscosity does not become too high when the fine cellulose fibers are mixed with rubber latex, making them easy to disperse, and as a rubber reinforcing material, the fine cellulose fibers can form a network structure in the rubber, thereby maintaining sufficient strength.
[0094] The degree of polymerization according to the viscosimetry using a copper ethylenediamine solution can be calculated by the following method: In the case of TEMPO-oxidized fine cellulose fibers, a reduction treatment is first performed. NaBH4 is added to a 1% aqueous dispersion of fine cellulose fibers at 10 wt% relative to the fine cellulose fibers, and the pH is adjusted to 10 with NaOH, after which the mixture is stirred for 4 hours for a reduction treatment. Ethanol is then added and the mixture is centrifuged, after which the supernatant is discarded and ethanol is added again, stirred and centrifuged. This process is repeated three times to recover the fine cellulose fibers, and reduced TEMPO-oxidized fine cellulose fibers are obtained.
[0095] The fine cellulose fibers are freeze-dried and dissolved in 0.5M copper ethylenediamine solution 1 to form solution 2. The viscosities of solutions 1 and 2 are measured using a capillary viscometer (Cannon-Fenske viscometer). The viscosity of solution 2 is η and the viscosity of solution 1 is η0, and the intrinsic viscosity [η] of the anion-modified pulp is calculated using the following formula.
[0096] Intrinsic viscosity [η]=(η / η0) / {c(1+0.28×η / η0)} (c is the concentration of fine cellulose fiber (g / dL))
[0097] Furthermore, the degree of polymerization DP is calculated by the following formula. Polymerization degree DP=intrinsic viscosity [η] / (5.7×10-3)
[0098] The fine cellulose fibers may be of one type or of a combination of two or more types.
[0099] [1.2 Rubber component] Examples of the rubber component include synthetic rubbers such as natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), chloroprene rubber (CR), acrylonitrile butadiene rubber (NBR), butyl rubber (IIR), ethylene propylene rubber (EPM), ethylene propylene diene rubber (EPDM), chlorosulfonated polyethylene (CSM), acrylic rubber (ACM), fluororubber (FKM), epichlorohydrin rubber (CO, ECO), urethane rubber (U), silicone rubber (Q), halogenated butyl rubber, and polysulfide rubber, but are not particularly limited thereto. Furthermore, thermoplastic elastomers such as polystyrene-based thermoplastic elastomers, polypropylene-based thermoplastic elastomers, polydiene-based thermoplastic elastomers, chlorine-based thermoplastic elastomers, and engineering plastics-based elastomers can also be used. The rubber component is preferably natural rubber (NR) or acrylonitrile butadiene rubber (NBR).
[0100] The rubber component may be one type alone or two or more types in combination.
[0101] [2. Method for producing intermediate kneaded product] The method for supplying a rubber composition of the present invention is characterized in that an intermediate kneaded product is obtained by molding a mixture of fine cellulose fibers having a number average fiber length of more than 400 nm and rubber latex into a sheet shape.
[0102] [2.1 Mixing process] [Microfine cellulose fiber dispersion] The fine cellulose fibers to be mixed with the rubber latex are preferably a dispersion obtained by dispersing the fine cellulose fibers in a dispersion medium (e.g., water, alcohol). The B-type viscosity (60 rpm) of such a fine cellulose fiber dispersion is usually 5,000 mPa·s or more, 6,000 mPa·s or more, 7,000 mPa·s or more, or 8,000 mPa·s or more, preferably 9,000 mPa·s or more, 10,000 mPa·s or more, more preferably 11,000 mPa·s or more, or 12,000 mPa·s or more. The upper limit is usually 100,000 or less, preferably 70,000 or less, more preferably 50,000 mPa·s or less. The solids concentration of the fine cellulose fiber dispersion (concentration of fine cellulose fibers) is not particularly limited, but is usually 1.5% or more, preferably 1.7% or more, more preferably 1.9% or more or 2.0% or more, and the upper limit is usually 20.0% or less, preferably 15.0% or less, more preferably 10.0% or less or 5.0% or less. The viscosity can be adjusted by the solids concentration, dispersion conditions, the physical properties of the fine cellulose fibers, the size, etc.
[0103] [Rubber latex] The rubber latex used in the mixing step may be an aqueous dispersion of a rubber component. The rubber latex can be prepared by dispersing a rubber component in water by a conventional method. The viscosity of the rubber latex is not particularly limited, but is usually 5 or more, preferably 10 mPa·s or more, and more preferably 15 mPa·s or more, and the upper limit is usually 400 mPa·s or less or 300 mPa·s or less, preferably 200 mPa·s or less, and more preferably 100 mPa·s or less. The amount of the solvent (water) for the rubber latex is usually 10 to 1000 parts by mass per 100 parts by mass of the rubber component (the total amount when two or more rubber components are used).
[0104] [Other ingredients] As the raw materials of the rubber composition, raw materials other than the fine cellulose fibers and the rubber component may be used. Other ingredients include dispersants, solvents and rubber additives.
[0105] [Dispersant] The dispersant can be used together with the fine cellulose fibers to improve dispersibility, for example, when the fine cellulose fibers are in a dry state. Examples of the dispersant include water-soluble polymers and surfactants, and water-soluble polymers are preferred. When the fine cellulose fibers are chemically modified cellulose fibers, the water-soluble polymers cover the low charge density areas on the surface, suppressing the formation of hydrogen bonds and preventing aggregation of the fine cellulose fibers during drying.
[0106] -Water-soluble polymer- It is believed that the water-soluble polymer penetrates between the fibers of the fine cellulose fibers and increases the distance between the fibers, thereby suppressing the aggregation of the fine cellulose fibers after drying. Examples of the water-soluble polymer include cellulose derivatives (carboxymethylcellulose, methylcellulose, hydroxypropylcellulose, ethylcellulose), xanthan gum, xyloglucan, dextrin, dextran, carrageenan, locust bean gum, alginic acid, alginates, pullulan, starch, potato starch, kudzu starch, processed starch (cationized starch, phosphorylated starch, phosphate crosslinked starch, phosphate monoesterified phosphate crosslinked starch, hydroxypropyl starch, hydroxypropylated phosphate crosslinked starch, acetylated adipic acid crosslinked starch, acetylated phosphate crosslinked starch, acetylated oxidized starch, sodium octenyl succinate starch, acetate starch, oxidized starch), corn starch, gum arabic, locust bean gum, gellan gum, polydextrose, pectin, chitin, and water-soluble chitin. , chitosan, casein, albumin, soy protein lysate, peptone, polyvinyl alcohol, polyacrylamide, sodium polyacrylate, polyvinylpyrrolidone, polyvinyl acetate, polyamino acids, polylactic acid, polymalic acid, polyglycerin, rosin-based sizing agents, petroleum resin-based sizing agents, urea resins, melamine resins, epoxy resins, polyamide resins, polyamide-polyamine resins, polyethyleneimine, polyamines, vegetable gums, polyethylene oxides, hydrophilic crosslinked polymers, polyacrylates, starch-polyacrylic acid copolymers, tamarind gum, guar gum, colloidal silica, and mixtures of one or more thereof. Cellulose derivatives are preferred because of their high affinity with chemically modified fine cellulose fibers, and carboxymethylcellulose or a salt thereof is more preferred. The water-soluble polymer may be one type or a combination of two or more types.
[0107] -Surfactants- Examples of surfactants include, but are not limited to, nonionic surfactants such as fatty acid salts, higher alkyl sulfates, alkylbenzene sulfonates, higher alcohols, alkylphenols, and alkylene oxide adducts of fatty acids, anionic surfactants, cationic surfactants, amphoteric surfactants, organic solvents, proteins, enzymes, natural polymers, synthetic polymers, etc. The surfactant may be one type or a combination of two or more types.
[0108] [solvent] The solvent may be, for example, an aqueous solvent. The aqueous solvent is a solvent that is used to dissolve fine cellulose fibers and rubber. The aqueous solvent can be, for example, water, Water-soluble organic solvents or mixed solvents of these can be used. Fine cellulose fibers are hydrophilic. Therefore, water is preferred. By using water, a good dispersion state can be obtained during dispersion. The aqueous solvent may contain a non-water-soluble organic solvent to the extent that the effect of the invention is not impaired. good.
[0109] The water-soluble organic solvent may be any organic solvent that can be dissolved in water, and examples thereof include lower alcohols having 1 to 4 carbon atoms (e.g., methanol, ethanol, 2-propanol, butanol), glycerin, acetone, methyl ethyl ketone, 1,4-dioxane, N-methyl-2-pyrrolidone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, acetonitrile, and combinations thereof. Among these, lower alcohols having 1 to 4 carbon atoms are preferred, methanol, ethanol, and 2-propanol are more preferred, and from the viewpoints of safety and availability, methanol and ethanol are even more preferred, and ethanol is even more preferred.
[0110] The amount of the water-soluble organic solvent in the mixed solvent is not particularly limited, but is preferably 10% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more. The upper limit is preferably 95% by mass or less, and more preferably 90% by mass or less.
[0111] [Rubber additives] Examples of rubber additives include additives used for crosslinking rubber components. Crosslinking is generally performed by a vulcanization system that uses a crosslinking agent (vulcanizing agent) such as sulfur or a sulfur donor compound (e.g., sulfur halide) in combination with various general-purpose vulcanization accelerators such as sulfenamide-based and thiuram-based compounds. The crosslinking agent is not limited to a sulfur-based vulcanizing agent. Examples of crosslinking agents other than vulcanizing agents include organic peroxides, quinone dioximes, organic polyamine compounds, alkylphenol resins having methylol groups; compounds containing crosslinking groups such as isocyanate groups, carbodiimide groups, oxazoline groups, aziridine groups, and epoxy groups, polyfunctional cations, and compounds containing polyvalent metals. Examples of organic peroxides that can be used include commonly used compounds such as tert-butyl peroxide, dicumyl peroxide, tert-butylcumyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 1,3-di(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butylperoxybenzoate, tert-butylperoxyisopropylcarbonate, and n-butyl-4,4-di(tert-butylperoxy)valerate. In the case of organic peroxide crosslinking, it is preferable to use a polyfunctional unsaturated compound, for example, triallyl isocyanurate, triallyl cyanurate, triallyl trimellitate, trimethylolpropane trimethacrylate, or N,N'-m-phenylene bismaleimide in combination.
[0112] The content of the crosslinking agent is preferably 0 parts by mass or more per 100 parts by mass of the rubber component. The upper limit is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less. However, in the present invention, even if a vulcanizing agent or the like is contained, the effect of the present invention can be more effectively exhibited by being unvulcanized without being subjected to vulcanization treatment (heat treatment after addition of vulcanizing agent).
[0113] The rubber additives are not limited to the above examples, and examples thereof include vulcanization accelerators (e.g., zinc oxide, sulphuric acid, etc.). stearic acid), surfactants (cationic surfactants, anionic surfactants, non-ionic surfactants surfactants, amphoteric surfactants), reinforcing agents (e.g., carbon black, silica), silanes Coupling agents, hydrophobizing agents, oils, hardening resins, waxes, anti-aging agents, and colorants. The content of each agent is not particularly limited.
[0114] The weight ratio of the fine cellulose fiber to the rubber component is preferably 1 phr or more, more preferably 5 phr or more, and even more preferably 10 phr or more, relative to the rubber component (solid content). This allows the effect of improving tensile strength to be fully expressed. The upper limit is preferably 70 phr or less, more preferably 50 phr or less, and even more preferably 30 phr or less. This allows the processability in the manufacturing process to be maintained, the dispersion of the fine cellulose fiber in the rubber to be good, and there is little crimping during shipping.
[0115] [Method of manufacturing the mixture] The method for producing the mixture is not particularly limited, but examples thereof include a method in which fine cellulose fibers, a rubber component, and other raw materials (e.g., a solvent) used as necessary are added and stirred. The fine cellulose fibers are preferably used as a dispersion (e.g., an aqueous dispersion), and the dispersion may contain a dispersant as necessary. The rubber component is preferably added as a rubber latex. Stirring may be performed using equipment such as a homodisper or a super mixer.
[0116] [2.2 Drying process] In the drying step, the mixture can be dried by a known drying method such as drum drying, natural drying, oven drying, freeze drying, spray drying, pulse combustion, etc., with drum drying being particularly preferred.
[0117] [Drum dryer] A drum dryer is a dryer equipped with a rotatable drum (cylinder) and a doctor blade (knife, scraper knife) capable of scraping off the material on the drum while the drum is rotating. The drum can be heated by introducing a heat medium (e.g., steam) into the drum (e.g., made of metal). When a sample to be treated (liquid) is continuously supplied to the preheated rotating drum surface and the sample is attached to the drum surface in the form of a thin film, the water in the sample evaporates and condenses during rotation, causing the sample to dry, and the sample can be scraped off from the drum surface with the doctor blade to obtain a dried material. The drum dryer may further be equipped with a feeder that supplies the sample (liquid) to the drum surface.
[0118] [Drying temperature] The temperature condition during drying is usually 70°C or higher, preferably 80°C or higher, more preferably 90°C or higher, 100°C or higher, or 110°C or higher. This allows the drying process to proceed efficiently. The upper limit is usually 150°C or lower, preferably 140°C or lower, more preferably 135°C or lower. This allows the denaturation of cellulose due to heat to be suppressed, and the deterioration of mechanical properties after molding of the resulting dried body to be avoided. Therefore, by usually setting the temperature at 70 to 150°C, preferably 80 to 140°C, more preferably 90 to 135°C, 100 to 135°C, or 110 to 135°C, the drying process can be proceeded efficiently and the deterioration of mechanical properties can be avoided. In this specification, the temperature during drying means the temperature of the drum surface of a drum dryer.
[0119] The mixed liquid may be at room temperature when supplied to the drum dryer, but may be preheated. When heating, the heating temperature is, for example, 40° C. or more, 50° C. or more, 60° C. or more, or 65° C. or more. There is no particular upper limit, and the heating temperature may be 70° C. or less.
[0120] The moisture content of the dried product after the drying step is usually 8% by mass or less, preferably 5% by mass or less. This range improves the workability in the subsequent mixing step (e.g., kneading and mixing). There is no particular lower limit, and it is sufficient to be 0% by mass (bone dry) or more.
[0121] [2.3 Sheet-like intermediate kneaded material] The dried product obtained above can be rolled several times using a roll kneading device such as an open roll to obtain an intermediate kneaded product formed into a sheet shape. The roll kneading device can be a two-roll or three-roll device.
[0122] The clearance can be set in the range of 0.1 to 10 mm. Since the volume change of the dried material before and after the roll treatment is large and the overload is large, it is preferable to gradually reduce the clearance within the above range when the roll treatment is repeated multiple times so as to satisfy the relationship A>B>C, for example, when the clearance during the first roll treatment is A, the clearance during the second roll treatment is B, and the clearance during the third roll treatment is C.
[0123] [2.2 Packaging process] It is important that the intermediate kneaded product molded into a sheet is laminated into two or more layers by folding / cutting / rolling, etc., and then packaged. Normally, unvulcanized rubber compositions are easily pressed together, so it is difficult to laminate and package them in sheet form (which significantly reduces work efficiency), and it is necessary to apply a release agent or attach a protective film, or to package them as a lump such as a bale, but these processes are economical and inefficient.
[0124] Since the intermediate kneaded product of the present invention contains fine cellulose fibers having a number-average fiber length of 400 nm or more, the surface has a moderate stiffness (unevenness), which prevents compression and makes it possible to stack and package the unvulcanized sheet-like intermediate kneaded product without reducing work efficiency.
[0125] Regarding the lamination form, when the sheet-like material is folded or cut, it may be laminated in either the vertical or horizontal direction, and a lamination form suitable for packaging can be appropriately performed. When laminating in a roll form, for example, the sheet-like intermediate kneaded material can be directly wound around a core so as to form multiple layers. There is no particular upper limit on the number of layers, and it can be appropriately adjusted within the range that can be packed in the packaging material.
[0126] As for the packaging form, it is sufficient if the multiple-layered intermediate kneaded product can be packaged in an outer bag that protects it from impact, and such an outer bag can be appropriately selected from those that are normally used for packaging, such as cardboard boxes, containers, polystyrene foam boxes, plastic boxes, and impact-resistant bags.
[0127] In order to prevent the stacked intermediate kneaded products from collapsing, they can be fixed with an inner bag, sheet, band, etc. as appropriate before being packed in an outer bag.
[0128] [2.3 Transfer process] In the method for supplying a rubber composition of the present invention, the packaged intermediate mixture is transported from a first kneading place where the above-mentioned mixing step is carried out to a second kneading place where the below-mentioned dilution step is carried out. The form of transportation is not particularly limited and may be selected from a usual distribution method.
[0129] [2.4 Dilution process] The intermediate mixture transferred to the second mixing location is diluted by mixing with another rubber latex, further mixed, and molded into a desired shape. The other rubber latex is the same as that described in [1.2 Rubber component], but is preferably the same rubber component as the rubber latex used in the production of the intermediate mixture.
[0130] As the method for dilution kneading, any ordinary rubber kneading method can be used without limitation, and examples thereof include open kneading methods such as roll kneading, and closed kneading methods such as a Banbury mixer or kneader.
[0131] It is preferable to dilute the rubber composition after dilution and kneading so that the content of the fine cellulose fibers in the rubber composition is 0.01 to 20 parts by weight, preferably 0.1 to 15 parts by weight, and more preferably 1 to 10 parts by weight, per 100 parts by weight of rubber.
[0132] According to the rubber composition supply method of the present invention, an intermediate mixture in which fine cellulose fibers are dispersed at a high concentration is prepared in a first kneading location, and then, in a second kneading location, a rubber composition in which fine cellulose fibers are adequately dispersed can be obtained by simple dilution kneading.
[0133] As described above, since the average fiber length of the fine cellulose fibers is 400 nm or more, the laminated sheet-like rubber composition is prevented from being pressed against each other even during transportation, so that the sheet-like intermediate kneaded material can be easily removed from the package at the second kneading location. Even during dilution kneading, the sheet-like intermediate kneaded material can be roll kneaded as is, making it possible to carry out a simple process.
[0134] [Other additives] The rubber composition may contain additives as necessary during kneading. For example, additives used for crosslinking rubber components when obtaining rubber products can be mentioned. Crosslinking is generally performed by a vulcanization system using a crosslinking agent (vulcanizing agent) such as sulfur or a sulfur donor compound (e.g., sulfur halide) in combination with various general-purpose vulcanization accelerators such as sulfenamide-based and thiuram-based compounds. The crosslinking agent is not limited to a sulfur-based vulcanizing agent. Examples of crosslinking agents other than vulcanizing agents include organic peroxides, quinone dioximes, organic polyamine compounds, alkylphenol resins having methylol groups; compounds containing crosslinking groups such as isocyanate groups, carbodiimide groups, oxazoline groups, aziridine groups, and epoxy groups, polyfunctional cations, and compounds containing polyvalent metals. Examples of organic peroxides that can be used include commonly used compounds such as tert-butyl peroxide, dicumyl peroxide, tert-butylcumyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 1,3-di(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butylperoxybenzoate, tert-butylperoxyisopropylcarbonate, and n-butyl-4,4-di(tert-butylperoxy)valerate. In the case of organic peroxide crosslinking, it is preferable to use a polyfunctional unsaturated compound, for example, triallyl isocyanurate, triallyl cyanurate, triallyl trimellitate, trimethylolpropane trimethacrylate, or N,N'-m-phenylene bismaleimide in combination.
[0135] The content of the crosslinking agent is preferably 1.0 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 1.7 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less.
[0136] Examples of the vulcanization accelerator include Nt-butyl-2-benzothiazole sulfenamide and N-oxydiethylene-2-benzothiazolylsulfenamide. The content of the vulcanization accelerator is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less.
[0137] The additives are not limited to the above examples, and examples thereof include vulcanization accelerators (e.g., zinc oxide, stearic acid), surfactants (cationic surfactants, anionic surfactants, nonionic surfactants, amphoteric surfactants), reinforcing agents (e.g., carbon black, silica), silane coupling agents, hydrophobizing agents, oils, cured resins, waxes, antioxidants, and colorants. The content of the optional components may be appropriately determined depending on conditions such as the type of the optional components, and is not particularly limited.
[0138] The additives described above can also be used appropriately for the intermediate kneaded product. However, since the intermediate kneaded product is subsequently diluted and kneaded to produce the desired rubber composition, it is preferable to keep the intermediate kneaded product unvulcanized even if additives are added. EXAMPLES
[0139] Examples of the present invention will be described below, but the present invention is not limited to these.
[0140] TENPO oxidized CNF was produced as follows. In the following production examples, the amount of carboxyl groups, average fiber length, and average fiber diameter were measured by the methods described above.
[0141] <Production Example 1> 5000g (bone dry) of bleached unbeaten kraft pulp (brightness 85%) derived from coniferous trees was added to 50L of an aqueous solution in which 7800mg of TEMPO (Sigma Aldrich) and 755g of sodium bromide were dissolved, and the mixture was stirred until the pulp was uniformly dispersed. An aqueous solution of sodium hypochlorite was added to the reaction system to a concentration of 6.0mmol / g to initiate the oxidation reaction. The pH of the system decreased during the reaction, but 3M aqueous sodium hydroxide was added successively to adjust the pH to 10. The reaction was terminated when the sodium hypochlorite was consumed and the pH of the system did not change. The mixture after the reaction was filtered through a glass filter to separate the pulp, and the pulp was thoroughly washed with water to obtain oxidized pulp. The pulp yield at this time was 90%, and the time required for the oxidation reaction was 90 minutes. The oxidized pulp obtained in the above process was adjusted to 1.0% (w / v) with water and defibrated twice with an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain a dispersion of oxidized CNF. The carboxyl group amount of the obtained TEMPO oxidized CNF was 1.42 mmol / g, the length-weighted average fiber length was 567 nm, and the length-weighted average fiber diameter was 2.4 nm.
[0142] The concentration of the TEMPO-oxidized CNF prepared above was adjusted to obtain a slurry containing 1% CNF. The B-type viscosity (25°C, 60 rpm) of the slurry was measured using the following method: After stirring at 3000 rpm for 5 min with a homodisper, the viscosity measurement was started (60 rpm), and the viscosity value after 3 min was recorded as 5180 mPa s.
[0143] <Production Example 2> 40 kg (bone-dry) of bleached unbeaten kraft pulp (whiteness 85%: Nippon Paper Industries Co., Ltd.) derived from conifers was added to 4000 L of an aqueous solution containing 312 g (0.05 mmol per g of bone-dry cellulose) of TEMPO (Sigma Aldrich) and 4112 g (1.0 mmol per g of bone-dry cellulose) of sodium bromide, and the mixture was stirred until the pulp was uniformly dispersed. An aqueous solution of sodium hypochlorite was added to the reaction system so that the sodium hypochlorite concentration was 5.5 mmol per 1 g of bone-dry cellulose, and the oxidation reaction was started at room temperature. The pH of the system decreased during the reaction, but 3 M aqueous solution of sodium hydroxide was added successively to adjust the pH to 10. The reaction was terminated when the sodium hypochlorite was consumed and the pH of the system no longer changed. After adding hydrochloric acid to the reaction mixture to adjust the pH to 2, the pulp was thoroughly washed by repeated dehydration and dilution with water, and finally dehydrated until the pulp solids concentration reached 20% by weight to obtain a carboxy-modified pulp (TEMPO oxidized pulp).
[0144] The obtained carboxy-modified pulp was dispersed in ion-exchanged water, and sodium hydroxide was added and stirred to obtain an aqueous dispersion of carboxy-modified pulp with a pH of 8.8 and a solid content of 2% by weight. 74 kg of this aqueous dispersion of carboxy-modified pulp was beaten by circulating it for 10 minutes using a single disc refiner (Aikawa Iron Works Co., Ltd., 14-inch lab refiner (RF-14 type), plate: blade width: 0.6 mm, groove width: 1.0 mm) with a clearance of 0.23 to 0.25 mm, to obtain a TEMPO-oxidized MFC. The length-weighted average fiber length was 59 μm, the average fiber diameter was 5.1 μm, and the carboxyl group content was 1.42 mmol / g.
[0145] <Example 1> In the first kneading area, 325 g of the aqueous dispersion of TEMPO-oxidized CNF with a solid content concentration of 1% obtained in Production Example 1 and 100 g of natural rubber latex (product name: HA Latex, Resitex Corporation, solid content concentration 65%) were mixed to make the mass ratio of the rubber component (solid content of natural rubber latex) to the solid content of TEMPO-oxidized CNF 100:20, and the mixture was stirred for 10 minutes with a TK homomixer (8000 rpm). The mixture was then dried in a heating oven at 70°C for 5 hours.
[0146] The above dried product was passed through an open roll (manufactured by Kansai Roll Co., Ltd.) about five times so as to be visually uniform, to obtain a sheet of an unvulcanized intermediate kneaded product 1.
[0147] The obtained sheet of intermediate kneaded material 1 was cut to a length of about 20 cm, and was firmly laminated while applying pressure so as to form 5 to 10 layers so as not to be bulky. The laminated cut sheets were placed in a polyethylene bag that would become the inner bag, and fixed so as not to shift. Two sets of stacks of laminated sheets filled in this inner bag were packed in a cardboard box of appropriate size. Then, it was left at room temperature for one week.
[0148] The cardboard box containing the intermediate kneaded material 1 was then transported by truck to a rubber processing plant, which was the second kneading location. At the second kneading location, the intermediate kneaded material was visually inspected for the presence or absence of crimping when it was removed from the package, and the workability (ease of removal from the package and ease of subsequent processing) was evaluated according to the following criteria.
[0149] <Presence or absence of crimping> A: No crimping was observed. ×: Crimping was observed.
[0150] <Workability> 〇: It can be easily removed from the packaging, and since the stacked sheets are not laminated, they can be easily separated one by one, making it easy to work with. ×: The sheets were difficult to remove from the package because they were pressed together, and it was difficult to separate them one by one.
[0151] The intermediate kneaded material 1 was diluted and kneaded by rolling it multiple times with an open roll with a pure rubber sheet made from natural rubber latex (product name: HA Latex, Resitex, solid content concentration 65%) in a mass ratio of 20:80 to obtain a rubber composition containing 5 parts by weight of fine cellulose fibers.
[0152] <Example 2> Intermediate kneaded material 2 was obtained in the same manner as in Example 1, except that the mixed liquid of TEMPO oxidized CNF and natural rubber latex was dried using a double-drum type drum dryer (surface temperature 130°C / rotation speed 1 rpm). The intermediate kneaded material 2 obtained was packaged in the same manner as in Example 1 and left for one week, after which it was visually inspected for the presence or absence of compression at the transport destination.
[0153] <Example 3> An intermediate kneaded material 4 was obtained in the same manner as in Example 1, except that the TEMPO oxidized MFC obtained in Production Example 2 was used instead of the TEMPO oxidized CNF. The intermediate kneaded material 4 obtained was packaged in the same manner as in Example 1, and after being left for one week, the presence or absence of compression at the transport destination was visually confirmed.
[0154] <Comparative Example 1> An intermediate kneaded material 3 was obtained in the same manner as in Example 1, except that TEMPO oxidized CNF was not mixed. The obtained intermediate kneaded material 3 was packaged in the same manner as in Example 1, and after leaving it for one week, the presence or absence of compression at the transport destination was visually confirmed.
[0155] [Table 1]
[0156] According to the method for supplying a rubber composition of the present invention, by using an intermediate kneaded product in which fine cellulose fibers having an average fiber length of more than 400 nm are dispersed at a high concentration as a master batch, a rubber composition in which fine cellulose is dispersed can be easily obtained even in a rubber processing plant.
Claims
1. A method for supplying a rubber composition containing fine cellulose fibers, comprising the steps of: In a first kneading place, an intermediate kneaded product is obtained by molding a mixture of fine cellulose fibers having a length-weighted average fiber length of more than 400 nm and rubber latex into a sheet shape, The intermediate mixture is transported to a second mixing location in a multi-layered package form, The method for supplying a rubber composition comprises diluting the intermediate mixture in a second mixing location and further mixing the mixture.
2. 2. The method for supplying a rubber composition according to claim 1, wherein the fine cellulose fibers have a length-weighted average fiber diameter of 1 nm or more and 20 nm or less.
3. 3. The method for supplying a rubber composition according to claim 1, wherein the intermediate kneaded product contains fine cellulose fibers in an amount of 10 to 40% by weight.
4. 4. The method for supplying a rubber composition according to claim 1, wherein the intermediate kneaded product is laminated and packaged without being subjected to treatments such as coating with a release agent or attaching a protective film.
5. 5. The method for supplying a rubber composition according to claim 1, wherein the intermediate mixture is unvulcanized.
6. 3. The method for supplying a rubber composition according to claim 1, wherein the intermediate mixture is formed into a sheet by a roll kneading method.
7. 3. The method for supplying a rubber composition according to claim 1, wherein the fine cellulose is anion-modified.
8. 3. The method for supplying a rubber composition according to claim 1, wherein the fine cellulose has not been subjected to a hydrophobic treatment.
Citation Information
Patent Citations
Master batch and manufacturing method of rubber composition
JP2018193465A
Toothed belt
JP2019143813A
Rubber composition and process for producing same
JP2019172858A
Resin composition and method for producing the same
JP2023011541A
Masterbatch of rubber / short fiber, manufacturing method for the same and pneumatic tire using the same
JP2006206864A